2016
DOI: 10.7845/kjm.2016.5049
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phytoestrogen contents and antioxidant activities during fermentation of soybean-powder milks prepared from different soybean cultivars by Lactobacillus plantarum P1201

Abstract: This study evaluated the changes of phytoestrogen contents and antioxidant activities of soybean-powder milk (SPM) prepared from yellow soybean during fermentation with Lactobacillus plantarum P1201. In consequence, the levels of total phenolic and isoflavone-aglycone contents, ABTS and DPPH radical-scavenging activities, and FRAP assay values increased, while isoflavone-glycoside contents decreased during fermentation. The highest levels of daidzein, glycitein, and genistein were present in the Daepung SPM at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…FSM/AM (75:25)-Bc achieved higher FRAP activity than Bg during 21 days of storage. Both Bg & Bc showed β-glycosidase activity during fermentation (Hwang et al, 2016). Karaçalı et al (2018) reported that B. longum and B. lactis are capable to ferment soymilk with a DPPH activity of ~16%.…”
Section: Antioxidant Properties (Dpph Fic and Frab) In Fermented Plan...mentioning
confidence: 99%
“…FSM/AM (75:25)-Bc achieved higher FRAP activity than Bg during 21 days of storage. Both Bg & Bc showed β-glycosidase activity during fermentation (Hwang et al, 2016). Karaçalı et al (2018) reported that B. longum and B. lactis are capable to ferment soymilk with a DPPH activity of ~16%.…”
Section: Antioxidant Properties (Dpph Fic and Frab) In Fermented Plan...mentioning
confidence: 99%